2004
DOI: 10.1159/000078210
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes and speciation in <i>Mus musculus domesticus</i>

Abstract: Thirty years after its identification, the model of chromosomal speciation in Mus musculus domesticus is reevaluated using the methods of population biology, molecular cytogenetics and functional genomics. Three main points are considered: (1) the structural predisposition of M. m. domesticus chromosomes to Robertsonian fusion; (2) the impediment of structural heterozygosity to gene flow between populations of mice with karyotypes rearranged by Robertsonian fusion and between them and populations with the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 75 publications
(89 reference statements)
1
28
0
10
Order By: Relevance
“…It is known that crosses between chromosomal variants can result in hybrid inviability or impaired fitness (Capanna and Castiglia 2004). Speciation rates differ considerably between birds and mammals with the evolution of post-zygotic incompatibility being $10 times slower in birds than in mammals (Price and Bouvier 2002;Fitzpatrick 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that crosses between chromosomal variants can result in hybrid inviability or impaired fitness (Capanna and Castiglia 2004). Speciation rates differ considerably between birds and mammals with the evolution of post-zygotic incompatibility being $10 times slower in birds than in mammals (Price and Bouvier 2002;Fitzpatrick 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on, for example, Mus musculus domesticus have shown that crosses between chromosomal variants can result in hybrid inviability or impaired fitness (Capanna and Castiglia, 2004). The formation of post-zygotic incompatibility is substantially slower in birds than in mammals (Price and Bouvier, 2002;Fitzpatrick, 2004;Price, 2008), which may be explained by the slow rate of chromosomal rearrangement in birds.…”
Section: Synteny and Gene Ordermentioning
confidence: 99%
“…This, together with its effects in the reduction of both fertility and recombination (especially in animals with Rb translocations in heterozygosis), suggests that Rb fusions may play an important role in speciation (e.g. Rieseberg 2001, Capanna & Castiglia 2004. Moreover, several studies have supported the idea that Rb fusions cause reproductive isolation in a number of mammal species (Theiler & Blanco 1996, De Oliveira et al 2000, Rogatcheva et al 2000, Fernández-Donoso et al 2001, Jadwiszczak & Banaszek(Gü ndüz et al 2001, Sans-Fuentes et al 2007, and they can act as isolating barriers between populations.…”
Section: Introductionmentioning
confidence: 99%